The Influence of Social Media Marketing and Service Quality on Customer Satisfaction Mediated by Price at PT Master Tritunggal Pratama - Galuh Al Birra; Ismail Razak; Partogi Soloan Samosir (Krisnadwipayana International Journal of Management Studies, 2025)
This study aims to: determine and analyze the influence of pemasaran sosial media on customer satisfaction at PT Master Tritunggal Pratama, determine and analyze the influence of service quality on customer satisfaction at PT Master Tritunggal Pratama, determine and analyze the influence of pemasaran sosial media on price at PT Master Tritunggal Pratama, determine and analyze the influence of pemasaran sosial media on price at PT Master Tritunggal Pratama, determine and analyze the influence of price on customer satisfaction at PT Master Tritunggal Pratama, determine and analyze the indirect influence of pemasaran sosial media on customer satisfaction through price at PT Master Tritunggal Pratama, determine and analyze the indirect influence of service quality on customer satisfaction through price at PT Master Tritunggal Pratama. The study was conducted at PT Master Tritunggal Pratama with a research sample of 65 respondents. The sampling technique used in this study was a saturated sampling technique. The data analysis method used descriptive analysis and path analysis. The results of the study show that: there is an influence of pemasaran sosial media on customer satisfaction at PT Master Tritunggal Pratama, there is an influence of service quality on customer satisfaction at PT Master Tritunggal Pratama, there is an influence of pemasaran sosial media on prices at PT Master Tritunggal Pratama, ) there is an influence of pemasaran sosial media on prices at PT Master Tritunggal Pratama, there is an influence of prices on customer satisfaction at PT Master Tritunggal Pratama, there is an indirect influence of pemasaran sosial media on customer satisfaction through prices at PT Master Tritunggal Pratama, there is an indirect influence of service quality on customer satisfaction through prices at PT Master Tritunggal Pratama.